An implementation of a device to assist the visually Impaired / blind people for easy navigation through bus. Issue 1 (February 2021) - Prasad, Dr. V. Siddeswara; Sagar, R
Abstract: Talking signs, control stick, echolocations are generally helpful in exploring the visually impaired people to arrive at their goal, but this can't be used for longer distance of travelling in the traffic. So a wireless sensor network is proposed to help the blind or visually impaired person to navigate easily through the bus in the traffic safely. The proposed system has two modules one is in the hand of blind and other inside the bus. Both the modules has a ZigBee transceiver. The bus arrival informati on is given from the ZigBee in the bus module to the ZigBee of the blind module. When the blind tells his destination through the microphone it is then recognized by the voice recognition software in the blind module. The input is then analyzed by the microcontroller and if it is matched with the stored data base the controller guides the blind to take the right bus to reach his/her desired destination otherwise he has to wait for other bus. The buzzer and LED is connected with the device inside the bus to alert the driver when the blind module starts communication with the device present in the bus. When the bus reached the destination, it is announced through earphone of the blind module with the help of voice synthesizer. Along with this the buzzer is ma de and LED glows to provide the much more alert to the blind to get down in his/her desired destination. So, this project not only helps the blind but also for the elder or senior people for their independent navigation.